Zirconium-based conversion coating modified by different amount of chitosan on hot-dip Zn-Al alloy coated steel sheet - Jie Pan; Ya-jing Ding; Rui-cheng Zhao; Jian Zhang; Yan Li (Corrosion Communications, 2023)
Chitosan (CTS) as an environment-friendly biological macromolecule was applied to investigate its effect in improving the property of zirconium-based Cr(III) conversion coating on Zn-55Al-1.6Si coated steel sheet (Zn55Al). High-resolution transmission electron microscope gave the key evidence that CTS can effectively wrap the main film-forming substances and participate in the construction of Zr@CTS-TCC. A comparative analysis of electrochemical measurements showed that the addition of 0.2 g·L–1 CTS can improve the corrosion resistance of Zr@CTS-TCC and decrease the surface density of micro defects. Surface spectroscopy characterization provided a theoretical explanation for the role of CTS as an electron supplier in reduction of Cr(VI). Results demonstrate the potential of CTS as an environmentally friendly and effective cross-linking additive, which provides an alternative approach in developing next generation of trivalent chromium or chromium-free passivator for nonferrous alloy and their coatings.